Effects of fertilisation and understory removal on aboveground and belowground carbon stocks in wet and dry moorlands in south-western France - Bon, Lucie; Augusto, Laurent; Gaudry, Jonathan; Bakker, Mark R.; Lambrot, Catherine; Milin, Sylvie; Trichet, Pierre; Fanin, Nicolas (European journal of forest research, 2023)
Forests provide essential ecosystem services such as wood production and soil carbon storage, which can be influenced by forest management. Fertilisation and understory removal are common practices set up in managed forests to reduce tree mortality and relieve trees from their main limitations, but their effects on belowground functioning and soil carbon storage are still unclear. In this study, we investigated the effects of phosphorus fertilisation, understory removal and their interaction on the carbon stored in the ecosystem and soil enzyme activities in two contrasting moorlands in south-western France (dry and wet moorlands) planted with maritime pines ( Pinus pinaster Ait.). In the wet moorland, we found that fertilisation and understory removal had a positive effect on tree biomass, but they did not affect soil carbon stocks nor carbon-related enzyme activities. In the dry moorland, understory removal had a significant positive effect on tree biomass and a strong negative effect on topsoil organic carbon stocks and carbon-related enzyme activities. Overall, understory removal did not affect total carbon stocks at the ecosystem scale due to compensatory effects between carbon pools, i.e. the increase in carbon stored in the aboveground biomass was cancelled by a decrease in carbon stored in the soil. These results highlight the importance of adapting forest practices depending on the environmental context and carbon sequestration objectives.